Enhancing creative thinking skills through project-based learning and SCAMPER: a study in Vietnam - Nguyen Thi Phuong Thanh; Le Huong Hoa (Institute of Advanced Engineering and Science, 2026)
Creative thinking skills (CTS) are essential 21st-century skills for adapting to the rapidly changing world. This study aims to investigate the effectiveness of project-based learning (PBL) and substitute, combine, adapt, modify, put to another use, eliminate, reverse (SCAMPER) in enhancing high school students’ CTS, including fluency, flexibility, originality, and usefulness. This quasi-experimental study involved 120 high school students from three classes at a public high school in Vietnam. The study employed a pretest-posttest control group design with one experimental group (n=40) and all two control groups (n=80). The creative engineering design assessment (CEDA) was used. The 15-week intervention involved students in PBL-SCAMPER, while two control groups (n=40 each) followed traditional instruction. One-way analysis of variance (ANOVA) revealed significant improvements in all CTS indicators for the experimental group (p<0.05), with the largest effect on usefulness (η²=0.27). These findings suggest that the PBL-SCAMPER provides a practical pedagogical framework for developing CTS, warranting broader implementation in high school education.